Human phosphatidylethanolamine-binding protein 4 promoted the radioresistance of human rectal cancer by activating Akt in an ROS-dependent way. - Jianming Qiu; Guangen Yang; Ali Lin; Zhong Shen; Dong Wang; Lei Ding (PLoS ONE, 2014)
Human phosphatidylethanolamine-binding protein 4(hPEBP4) is a novel anti-apoptosis molecule associated with the resistance of tumors to apoptotic agents. Here we sought to investigate the role of hPEBP4 in the radioresistance of rectal cancer. Immunohistochemistry analysis showed hPEBP4 was expressed in 27/33 of rectal cancer specimens, but only in 2/33 of neighboring normal mucosa. Silencing the expression of hPEBP4 with siRNA significantly reduced the clonogenic survival and enhanced the apoptosis of rectal cancer cells on irradiation. Instead, forced overexpression of hPEBP4 promoted its survival and decreased the apoptosis. Western blot showed hPEBP4 could increase the radiation-induced Akt activation, for which reactive oxygen specimen(ROS) was required. The radioresistance effect of hPEBP4 was reversed after given LY-294002 to inhibit Akt activation or antioxidant to abolish the ROS production. We also confirmed that effect of hPEBP4 in vivo with nude mice. Thus we concluded that hPEBP4, specifically expressed in rectal cancer cells, is associated with radioresistance of rectal cancer, implying that modulation of hPEBP4 may have important therapeutic implications in radiotherapy of rectal cancer.